Assistance and application of skewer smoothing and sharpening machine technology to increase the productivity of skewer craftsmen - Ilham Habibi; Dyah Adriantini Sintha Dewi; Marlina Kurnia (Community Empowerment, 2023)
Pasangsari Village, situated in Windusari District, stands out for its severe poverty levels, necessitating swift intervention to alleviate these challenges by leveraging its potential. Brigasan Kidul Hamlet, located within Pasangsari Village, is primarily inhabited by farmers. Despite its economic reliance on agriculture, the hamlet, positioned at an altitude of 100 meters above sea level, is densely covered with bamboo trees. Notably, bamboo serves as a crucial resource for the production of skewers, contributing to the local economy. The skewer industry, owing to its zero-waste production process, stands as a key factor in enhancing both capacity and product quality. The objective of this community service initiative is to enhance the quality and quantity of skewer products through technological implementation, thereby increasing the income of craftsmen in Brigasan Hamlet. The methods employed in this community engagement include socialization, the introduction of smoothing and sharpening machine technology, reinforcing administrative and institutional aspects, as well as mentoring, monitoring, and evaluation. The program's outcomes encompass an improvement in the quality and quantity of skewer products, coupled with the implementation of simple bookkeeping practices that facilitate the monitoring process.